Gender Representations in Moroccan Print Advertising - Yamani, Ahmed Kadiri Hassani (European Scientific Journal, ESJ, 2020)
Print advertising is a representative means of communication. Not only does it reflect a given culture but it also impacts the consumer attitudes. One of the main attitudes is gender roles, as the individual, hence the society, constantly seek if the representations and the expectations match. This paper explores gender representations in ten Moroccan magazines. Two of these magazines are men’s, two are women’s while the others are magazines of general interest. The paper also analyses how classical gender roles are still maintained or denied due to the increasing participation of women in the labour market. The findings reveal that there are overly stereotypical gender representations in print advertising. They also suggest that men’s and women’s magazines are not less gender stereotypic than general interest magazines.